2001
DOI: 10.1007/s004670100668
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring after renal transplantation in children

Abstract: Hypertension occurs commonly following renal transplantation and may cause end organ damage, such as cardiac hypertrophy. This study seeks to determine which features of hypertension are related to cardiac hypertrophy in children after renal transplantation. Ambulatory blood pressure monitoring (ABPM) was performed in 45 pediatric patients, 4.9+/-3.0 years after renal transplantation. ABPM data were related to clinical features and echocardiographic measurements. Hypertension was demonstrated in 33% of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
82
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 22 publications
20
82
3
Order By: Relevance
“…In our study, most children after renal transplantation were hypertensive and exhibited LVH. These data confirm other recent studies in children with renal transplants, describing arterial hypertension and LVH in similar percentages of the study populations [5,6,10,11].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, most children after renal transplantation were hypertensive and exhibited LVH. These data confirm other recent studies in children with renal transplants, describing arterial hypertension and LVH in similar percentages of the study populations [5,6,10,11].…”
Section: Discussionsupporting
confidence: 93%
“…As in other pediatric studies, 18,19 we found a high prevalence of abnormal BP detected by ABPM. The important observation in this study is that daytime SBP load was superior in predicting carotid artery compliance than casual BP.…”
Section: Discussionsupporting
confidence: 64%
“…to exclude hypertension) in chronic kidney disease. After renal transplantation, ABPM has proved to be more efficient than casual measurements [45] as renal transplantation is characterized by higher nocturnal BP values, a reversal of the diurnal rhythm [46] . Lack of nocturnal fall in BP and higher nocturnal BP values suggest target organ damage in primary hypertension [47] .…”
Section: Special Applications Of Abpmmentioning
confidence: 99%